Planetary boundaries for a blue planet - Nash, K; Cvitanovic, C; Fulton, E; Halpern, B; Milner-Gulland, E; Watson, R; Blanchard, J (Nature Publishing Group, 2017)
Concepts underpinning the planetary boundaries framework are being incorporated into multilateral discussions on sustainability, influencing international environmental policy development. Research underlying the boundaries has primarily focused on terrestrial systems, despite the fundamental role of marine biomes for earth system function and societal wellbeing, seriously hindering the efficacy of the boundary approach. We explore boundaries from a marine perspective. For each boundary we show how improved integration of marine systems influences our understanding of the risk of crossing these limits. Better integration of marine systems is essential if planetary boundaries are to inform earth system governance.